Evaluation of vitamin D status, vitamin D receptor expression, and innate immune mediators in COVID-19 - Missilmani, Ferdos; Maarabouni, Dima; Salem-Sokhn, Elie; Karras, Spyridon N.; Fakhoury, Hana M. A.; El Shamieh, Said (Frontiers in Endocrinology, 2025)
Background and objectivesThe Coronavirus disease 2019 (COVID-19) pandemic underscored the importance of identifying host factors that influence susceptibility to infection. Vitamin D signaling, mediated via its receptor (VDR), along with innate immune mediators such as antimicrobial peptides (e.g., DEFA1-3) and inflammatory chemokines (e.g., CCL20), plays a critical role in antiviral defense. This study aimed to determine how serum vitamin D status and gene expression of VDR, DEFA1-3, and CCL20 associate with COVID-19 risk in a Lebanese cohort.MethodsThis prospective observational study assessed serum vitamin D concentrations and nasopharyngeal gene expression in Lebanese participants tested for SARS-CoV-2 between January and March 2024. We enrolled 264 patients undergoing RT-qPCR (targeting ORF1, N, and E genes) and quantified serum 25-hydroxyvitamin D [25(OH)D]. In a subset of 70 individuals stratified by COVID-19 status, we measured VDR, DEFA1-3, CCL20, and GAPDH expression by RT-qPCR. Multiple logistic regression and Pearson correlation analyses were performed.ResultsSerum vitamin D levels and CCL20 expression were not significantly associated with COVID-19 status. Elevated VDR expression in nasopharyngeal tissue correlated with lower COVID-19 risk (OR = 0.40, p = 0.05) and inversely with 25(OH)D levels (r = –0.61, p = 0.04). Higher DEFA1–3 expression reduced COVID-19 risk by 81.6% (OR = 0.184, p = 0.012). Among COVID-19 negatives, VDR correlated with CCL20 (r = 0.59, p < 0.01); among positives, VDR correlated with DEFA1-3 (r = 0.45, p < 0.05).ConclusionOur findings reveal a complex interplay between systemic vitamin D status, local VDR expression, and innate inflammatory mediators in COVID-19. They support a model in which both micronutrient levels and tissue-specific vitamin D signaling modulate host susceptibility and disease severity.